Central bank communication by ??? - The economics of public policy leaks - Michael Ehrmann; Phillipp Gnan; Kilian Rieder (European Central Bank (ECB), 2023)
Leaks of confidential information emanating from public institutions have been the focus of a long-standing line of research. Yet, their determinants as well as their potential impact on public views and on policy effectiveness remain elusive. To address this gap, we study leaks from central banks because their effects are instantaneously reflected in financial markets. Based on a novel database of anonymous monetary policy leaks in the euro area as reported by newswires, we provide evidence that many of these leaks are likely placed by individual insiders with minority opinions. While we find that leaks have large effects on markets and weaken official policy announcements, our results also suggest that leaks do not lock in decision-makers, and that attributed communication can mitigate some of their effects.
Keywords: D83; E52; E58; G14; H83; 330; leaks; media; central bank communication; monetary policy; European Central Bank